In vivo antimalarial property of Markhamia lutea (Benth.) K. Schum leaf and stem-bark crude extracts and spectrophotometric evaluation of alkaloids, flavonoids, and phenolic contents - Casim Umba Tolo; Clement Olusoji Ajayi; Rapheal Wangalwa; Bruhan Kaggwa; Joshua Kiptoo; Martin Amanya (Infectious Diseases and Herbal Medicine)
Malaria is endemic to developing countries despite several efforts from the World Health Organization (WHO) and other organizations, and this has been attributed to many factors, including resistance to first-line antimalarial drugs. This study, therefore, evaluated phytochemical levels and antimalarial properties of Markhamia lutea (Benth.) K. Schum leaf and stem-bark extracted with various solvents as potential future alternative antimalarial drug development. Aqueous, ethanol, ethyl acetate, and methanol extracts from M. lutea leaf and stem-bark were evaluated for alkaloid, flavonoids, and phenolic levels using an ultraviolet-visible spectrophotometer. The extracts were further evaluated for antimalarial properties at 100-400 mg/kg on Plasmodium berghei NK65-induced mice using a 4-day test. The ethyl acetate leaf extract (50.8 µg/mg) gave the highest Quercetin Equivalent of Flavonoids (QEF), followed by ethanol and methanol leaf extracts with 46.2 and 47.5 µg/mg QEF, respectively. Methanol exhibited the highest level of Gallic Acid Equivalent of Phenolics (GAEP) with 213.4 µg/mg, while aqueous leaf extract was the lowest with 96.1 µg/mg GAEP. The results showed that aqueous and methanol leaf extract, ethanol, and methanol stem-bark extract possessed antimalarial activity with the lowest ED50 of 237.5 and 240.6, 233.8, and 236.6 mg/kg, respectively. The extracts of Markhamia lutea leaf and stem-bark demonstrated antimalarial properties with high contents of phenolic and flavonoid components, while the extracts showed no acute toxicity at the tested doses in the animals studied.